Reconstitution of the human U snRNP assembly machinery reveals stepwise Sm protein organization - Neuenkirchen, Nils (EMBO J, 2015)
The assembly of spliceosomal U snRNPs depends on the coordinated action of PRMT5 and SMN complexes in vivo. These trans-acting factors enable the faithful delivery of seven Sm proteins onto snRNA and the formation of the common core of snRNPs. To gain mechanistic insight into their mode of action, we reconstituted the assembly machinery from recombinant sources. We uncover a stepwise and ordered formation of distinct Sm protein complexes on the PRMT5 complex, which is facilitated by the assembly chaperone pICln. Upon completion, the formed pICln-Sm units are displaced by new pICln-Sm protein substrates and transferred onto the SMN complex. The latter acts as a Brownian machine that couples spontaneous conformational changes driven by thermal energy to prevent mis-assembly and to ensure the transfer of Sm proteins to cognate RNA. Investigation of mutant SMN complexes provided insight into the contribution of individual proteins to these activities. The biochemical reconstitution presented here provides a basis for a detailed molecular dissection of the U snRNP assembly reaction.